Design And Development of Online Admission System For Alquds Open University in Palestine - Malalha, Samer A.K (2012)
Student admissions are playing very important role in major activities of the any university as the basic requirement of the university is students and without students university cannot survive. An inefficient admission application system may reduce the number of admitted student in the esteemed university because if the admission system is slow and having many delays in the process. When considering Palestine students this is unfortunate, but when considering Palestinian international students it can mean the difference between success and failure because of the large sums of money each brings to the university’s economy. This project is to design and develop the under-graduate Palestinian international and local admission process at the University of Alquds Open University to develop an easy to use system that will significantly quicken and simplify this process. The interviews were conducted for the data collection, after that the design was made in UML for meeting the requirement of admission system. This admission system was developed by using JSP and MySQL. The system usefulness, quality of information and quality of interface were evaluated by distributing questionnaire to users and analysis on the data collected from questionnaire was analyzed by using SPSS software.